Meningkatkan Kompetensi Guru dalam Implementasi Kurikulum Merdeka melalui kegiatan In House Training (IHT) - Najemah, Nur (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
The Merdeka Curriculum is an innovation in the world of education which aims to create people who are competitive, creative and innovative. In its implementation, teachers have a very important role in ensuring the successful implementation of the Independent Curriculum. One way to improve teacher competence is through training. This research aims to improve the competency of MAN North Luwu teachers in implementing the independent curriculum through In House Training activities. Based on the results of observations, it was found that there was an increase in the average percentage of teacher competency in preparing learning administration from 77% in cycle I to 89% in cycle II and an increase in the average percentage of teacher competency in implementing learning that implemented the independent curriculum from 72% in cycle I to 87% in cycle II. The research results show that IHT activities can increase the competency of MAN North Luwu teachers in implementing the independent curriculum. IHT activities are one solution for increasing teacher competency because teachers who have broad insight will make a major contribution to the development of education in Indonesia.